Aberrant DNA methylations in chondrosarcoma. (November 2016) - Liu, Pei; Shen, Jacson K; Xu, Jianzhong; Trahan, Carol A; Hornicek, Francis J; Duan, Zhenfeng
Chondrosarcoma (CS) is the second most common primary malignant bone tumor. Unlike other bone tumors, CS is highly resistant to conventional chemotherapy and radiotherapy, thus resulting in poor patient outcomes. There is an urgent need to establish alternative therapies for CS. However, the etiology and pathogenesis of CS still remain elusive. Recently, DNA methylation-associated epigenetic changes have been found to play a pivotal role in the initiation and development of human cancers, including CS, by regulating target gene expression in different cellular pathways. Elucidating the mechanisms of DNA methylation alteration may provide biomarkers for diagnosis and prognosis, as well as novel treatment options for CS. We have conducted a critical review to summarize the evidence regarding aberrant DNA methylation patterns as diagnostic biomarkers, predictors of progression and potential treatment strategies in CS.